Potencial de Producción de Bioetanol a partir de Caña Panelera: Dinámica entre Contaminación, Seguridad Alimentaria y Uso del Suelo - Orjuela Castro, Javier Arturo; Huertas, Isaac; Figueroa García, Juan Carlos; Kalenatic, Dusko; Cadena, Katerine (Ingeniería, 2011)
As a solution to both oil high prices and pollution, grown-product fuel-generation (socalled biofuels) policies and projects have been promoted worldwide. Because raw materials involved in Bioethanol-and-Biodiesel making are used for human-consumption food production, producers face dichotomy regarding ground use, especially due to the prices paid to producers by either the energy or the food-production sector. Although the bio-fuel supply-chain dynamics have been studied from an incentives viewpoint [37], an understanding of the supply-chain prospective is necessary based on the dynamics of three aspects, namely ground use, pollution and food safety. The Panela cane is one of the raw materials with the best performance for Bioethanol production. Because Colombia is the highest per-capita Panela consumer (37,4 Kg/ Inhab) and the second producer in the world (after India), this article analyzes Bioethanol production dynamics based on Panela cane. Throughout the present article four aspects are discussed, namely Colombian Panela cane characterization, Colombian bio-fuel production current-projects development, oilprice influence on both Panela and sugar prices, and finally Panela cane bio-ethanol production.Historical data are forecasted through multivariate statistics and neural networks with the purpose of predicting future behavior within Panela cane production. In the context of the aforementioned dichotomy, Panela cane chain dynamics are studied based on the identification of both factors and variables, which are presented through a causal diagram